Development of a Self-Emulsifying Adjuvant for Use in Swine Vaccines - Rachel Madera; Yulia Burakova; Lihua Wang; Jishu Shi (Kansas Agricultural Experiment Station Research Reports, 2022)
Emulsion-based adjuvants are commonly used in animal vaccine formulations for several reasons including affordability, stability, and efficacy in inducing disease-protecting immune responses. Here we report a novel, cost-effective, stable, self-emulsifying adjuvant (SEA1) that is prepared by a simple low shear process or low-energy mixing without the use of expensive and complex proprietary equipment. Characterization of the SEA1 adjuvant showed good stability at different temperatures (4°C, 20°C, and 37°C) after one month of storage. Minimal changes in droplet size distribution, polydispersity index, Zeta potential and pH in 1-month-old SEA1 preparations were observed when compared with a fresh SEA1 preparation. SEA1 emulsion-based experimental vaccine preparations effectively stimulated humoral immunoglobulin (IgG) responses in mice and swine and were comparable to commercially available adjuvants Montanide ISA 201 and 206.
Keywords: swine; vaccine; adjuvant; classical swine fever